Innovative design and gearshift control for direct-drive electromagnetic gearshift system equipped with servo synchronizer. (April 2019) - Li, Bo; Ge, Wenqing; Yu, Xiao; Shao, Shilei; Liu, Haitao
Automated mechanical transmission has many advantages such as simple structure, high mechanical efficiency, and low cost. But the poor gearshift performance restricts the massive application of the automated mechanical transmission, and it can be improved through innovation of structure and control. To reduce the requirement of shift force and improve the shift performance, a new direct-drive electromagnetic gearshift system which consists of servo synchronizer and 2-degree-of-freedom electromagnetic actuator is adopted. The specific structure and working principle of the gearshift system including servo synchronizer are described, and the equation of force-amplifying ratio is deduced. Due to the complexity of the gearshift system and uncertainties of the gearshift process, active disturbance rejection control method is designed. The active disturbance rejection controller can eliminate the nonlinearity of the 2-degree-of-freedom actuator. The extended state observer can estimate and compensate the uncertainties, parameter variations, and external disturbances. Simulations are carried out, and the result comparison with proportional–integral–derivative controller indicates the superiority of the active disturbance rejection control method. Test bench and control system are developed to verify the performance of the newly designed system and control method. The experimental results show that, when the gearshift system is equipped with servo synchronizer, the driving force and the maximum volatility of driving force can be reduced by 35% and 5%, respectively, and the impact generated by active disturbance rejection control method is reduced by 36% compared with proportional–integral–derivative method. The new gearshift system achieves a better gearshift performance. Combined with the newly designed control strategy, the direct-drive electromagnetic gearshift system provides a new solution for automated mechanical transmission applications.